ETIKA MENURUT PANDANGAN MURTADA MUTAHHARI - Muhammad Yunan (AL-Fikr, 2015)
This article discusses the ethics according to Murtadha Mutahhari. To Murtada Mutahhari, human actions can be distinguished between acts naturally (normal) and act akhlaqi. Natural act is an act that does not make the perpetrators be worthy of praise, for example; a hungry will eat, drink thirsty, tired of break and so on. Type of acts of this nature is also made by animals. Find akhlaqi act is an act that deserves to be praised or flattered, the artistry that is identical to the (voluntary). In that sense, people will recognize the great value of an act akhlaqi. The question is not whether prices can be juxtaposed or aligned with the material, such as money or other goods, of any such material. The question is ranked higher in the human person.